Temperature Control After In-Hospital Cardiac Arrest: A Randomized Clinical Trial. Issue 18 (28th September 2022) - Wolfrum, Sebastian; Roedl, Kevin; Hanebutte, Alexia; Pfeifer, Rüdiger; Kurowski, Volkhard; Riessen, Reimer; Daubmann, Anne; Braune, Stephan; Söffker, Gerold; Bibiza-Freiwald, Eric; Wegscheider, Karl; Schunkert, Heribert; et al.
Abstract : Background: This study was conducted to determine the effect of hypothermic temperature control after in-hospital cardiac arrest (IHCA) on mortality and functional outcome as compared with normothermia. Methods: An investigator initiated, open-label, blinded-outcome-assessor, multicenter, randomized controlled trial comparing hypothermic temperature control (32-34°C) for 24 h with normothermia after IHCA in 11 hospitals in Germany. The primary endpoint was all-cause mortality after 180 days. Secondary end points included in-hospital mortality and favorable functional outcome using the Cerebral Performance Category scale after 180 days. A Cerebral Performance Category score of 1 or 2 was defined as a favorable functional outcome. Results: A total of 1055 patients were screened for eligibility and 249 patients were randomized: 126 were assigned to hypothermic temperature control and 123 to normothermia. The mean age of the cohort was 72.6±10.4 years, 64% (152 of 236) were male, 73% (166 of 227) of cardiac arrests were witnessed, 25% (57 of 231) had an initial shockable rhythm, and time to return of spontaneous circulation was 16.4±10.5 minutes. Target temperature was reached within 4.2±2.8 hours after randomization in the hypothermic group and temperature was controlled for 48 hours at 37.0°±0.9°C in the normothermia group. Mortality by day 180 was 72.5% (87 of 120) in hypothermic temperature control arm, compared with 71.2% (84 of 118) in the normothermia group (relative risk, 1.03 [95% CI, 0.79–1.40]; P =0.822). In-hospital mortality was 62.5% (75 of 120) in the hypothermic temperature control as compared with 57.6% (68 of 118) in the normothermia group (relative risk, 1.11 [95% CI, 0.86–1.46, P =0.443). Favorable functional outcome (Cerebral Performance Category 1 or 2) by day 180 was 22.5% (27 of 120) in the hypothermic temperature control, compared with 23.7% (28 of 118) in the normothermia group (relative risk, 1.04 [95% CI, 0.78–1.44]; P =0.822). The study was prematurely terminated because of futility. Conclusions: Hypothermic temperature control as compared with normothermia did not improve survival nor functional outcome at day 180 in patients presenting with coma after IHCA. The HACA in-hospital trial (Hypothermia After Cardiac Arrest in-hospital) was underpowered and may have failed to detect clinically important differences between hypothermic temperature control and normothermia. Registration: URL: https://www.clinicaltrials.gov ; Unique Identifier: NCT00457431.